PERCEPTIONS OF INDONESIAN PRACTICAL NURSES TOWARDS UPDATING CAPABILITY TO PROVIDE CARE: A QUALITATIVE STUDY - Fitri Arofiati; Khanitta Nuntaboot (Belitung Nursing Journal, 2017)
Background: Capability to provide care can be recognized as the combination of nursing knowledge, skills, and attitude of care which is dynamic. Objective: This study aims to explore the perceptions of practical nurses towards updating capability to provide care. Methods: A descriptive qualitative study was conducted to explore the deep understanding of practical nurses towards updating capability to provide care. Data were gathered using in-depth interview with 25 practical nurses from different areas of practices, three times focus group discussion (FGD) and participant-observation. Qualitative content analysis model was applied to anaylze the data. Result: There were two themes emerged from data: 1) internal perceptions of updating capacity to provide care, with three subthemes: having great expectation, being confidence as a professional nurse, and developing self-initiation, 2) external contexts driving perception of practicing nurses, with two subthemes: giving best care and acquiring requirement. Conclusions: The findings indicated that updating capacity to provide care supports practical nurses to provide better nursing services to patients and meet the regulation of nursing professionalism.